2014
DOI: 10.1186/s12912-014-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nurses and physicians towards nurse-physician collaboration in northwest Ethiopia: a hospital based cross-sectional study

Abstract: BackgroundCollaboration between professionals is important in health institutions where most activities are team-performed. Ineffective nurse-physician collaboration affects patient outcome, nurses’ job satisfaction and organizational cost and is challenged by personal, interpersonal and organizational factors. The main objective of this study was to assess attitudes of nurses and physicians towards nurse-physician collaboration and the level of satisfaction with regard to quality of collaboration between them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 18 publications
4
38
2
1
Order By: Relevance
“…(12) An environment in which physicians and nurses communicate effectively and where the teamwork favors positive outcomes of care deliver to patients and relatives reduces the tensions and dissatisfactions deriving from the work environment and reduces mental illness among the workers. (13)(14) When the nurses lack autonomy in their work environment, they present feelings of suffering, anguish, dissatisfaction, stress and mental health problems. Thus, they tend towards the use of alcohol, sedatives and other drugs to resist those situations.…”
Section: Discussionmentioning
confidence: 99%
“…(12) An environment in which physicians and nurses communicate effectively and where the teamwork favors positive outcomes of care deliver to patients and relatives reduces the tensions and dissatisfactions deriving from the work environment and reduces mental illness among the workers. (13)(14) When the nurses lack autonomy in their work environment, they present feelings of suffering, anguish, dissatisfaction, stress and mental health problems. Thus, they tend towards the use of alcohol, sedatives and other drugs to resist those situations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Iran indicated that near half (48%) of nurses reported their remarks concerning the patient's health are ignored by physicians [12]. In Ethiopia, a study conducted at Felegehiwot and Gondar referral hospitals showed that more than one-third of nurses (41%) rate their collaboration as poor and only (3%) of nurses rate it as excellent [13].…”
Section: Introductionmentioning
confidence: 99%
“…Like most developing countries, Ethiopia has inadequate healthcare resources but with a vast healthcare needs and with hospitals which are congested with patients placing tremendous pressure and heavy workload to the health care providers [13]. Apart from the government's effort to increase the number and quality of healthcare institutions, it is imperative to have a positive collaboration of nurses and midwives with physician though is not assessed adequately.…”
Section: Introductionmentioning
confidence: 99%
“…A vicious cycle is in evidence: lack of motivation or access to upto-date diabetes information results in poor and outdated knowledge, attitude and practices, which perhaps are the source of the physicians' poor regard for nurses' knowledge which so demotivated some nurses (Amsalu, Boru, Getahun, & Tulu, 2014). Lack of effective multidisciplinary collaboration, and disrespect from physicians, is clearly a disincentive to nurses to contribute to case discussions, possibly to further diabetes education (Burgess & Purkis, 2010).…”
Section: Discussionmentioning
confidence: 99%